Perceptions of the term “abstinence” among adolescents and young adults: a qualitative study on alcohol non-consumption in Switzerland - Diana Fernandes Palhares; Lorraine Chok; Joan-Carles Suris; Yara Barrense-Dias (Advances in Drug and Alcohol Research)
As part of a broader qualitative study aimed at understanding the experiences and opinions of adolescents and young adults (AYA) who do not drink alcohol in Switzerland, participants were questioned about their perceptions of the term “abstinence” in the context of alcohol non-consumption. Twelve focus groups were conducted with 63 participants (36 females, 27 males), aged between 14 years and 20 years. Participants were grouped by gender, age (based on Swiss alcohol laws), and drinking status (non-drinker or drinker). The discussions were recorded and transcribed, and thematic content analysis was used to identify and categorize key themes. The terms “abstinence,” “abstainer,” and “abstention” were generally considered unsuitable when describing young people who do not consume alcohol regardless of the drinking status of the participants. The connotation carried by the terms was mostly perceived as religious, sexual, negative and stigmatizing. “Abstinence” was considered more appropriate for adults who have stopped drinking due to alcohol-related issues. When referring to youths, terms such as “non-drinking,” “non-drinkers” or “alcohol non-consumption” were preferred, especially to better integrate non-drinking youths and positively highlight their choices in preventive and educational initiatives.